2022
DOI: 10.1002/ecs2.4156
|View full text |Cite
|
Sign up to set email alerts
|

Plant functional traits affect competitive vigor of pasture grasses during drought and following recovery

Abstract: Grassland biomass production is strongly linked with the timing and intensity of precipitation events. While the direct effects of precipitation patterns on grasses are well‐studied, less is known regarding plant–plant interactions during different phases of drought (i.e., dry down vs. recovery). Here, we examined how the intensity and timing of drought affected biomass production, traits related to growth rate and competitive vigor (specific leaf area [SLA], leaf dry matter content [LDMC], and height [HT]), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 90 publications
(109 reference statements)
0
5
0
Order By: Relevance
“…In their natural environments, biotic or abiotic stresses negatively regulate plant growth and development ( Guo et al., 2019 ; Tang et al., 2019 ; Wu and Li, 2019 ; Li et al., 2020 ; Zhang et al., 2021 ; Liu et al., 2022B ; Mostofa et al., 2022 ), which activates plant stress defense mechanisms ( Sun et al., 2011 ; Shabala et al., 2014 ; Chen et al., 2017 ; Guo et al., 2019 ; Wu and Li, 2019 ; Li et al., 2020 ; Li et al., 2021 ; Lv et al., 2021 ; Zhang et al., 2021 ; Chieppa et al., 2022 ; Liu et al., 2022a ; Solis et al., 2022 ; Wu et al., 2022 ) ( Figure 1 ). Likewise, in the life of the most prestigious industrial crop, cotton growth and development is often regulated by different stress conditions that initiate several defense mechanisms at the physiological, cellular, and molecular levels, which include a change in plant height and leaf size, upregulation of antioxidant defense enzymes, and increase in the levels of defense-related genes and proteins ( Nagamalla et al., 2021 ; Qamer et al., 2021 ).…”
Section: Proteomics and Stress Adaptation In Cottonmentioning
confidence: 99%
“…In their natural environments, biotic or abiotic stresses negatively regulate plant growth and development ( Guo et al., 2019 ; Tang et al., 2019 ; Wu and Li, 2019 ; Li et al., 2020 ; Zhang et al., 2021 ; Liu et al., 2022B ; Mostofa et al., 2022 ), which activates plant stress defense mechanisms ( Sun et al., 2011 ; Shabala et al., 2014 ; Chen et al., 2017 ; Guo et al., 2019 ; Wu and Li, 2019 ; Li et al., 2020 ; Li et al., 2021 ; Lv et al., 2021 ; Zhang et al., 2021 ; Chieppa et al., 2022 ; Liu et al., 2022a ; Solis et al., 2022 ; Wu et al., 2022 ) ( Figure 1 ). Likewise, in the life of the most prestigious industrial crop, cotton growth and development is often regulated by different stress conditions that initiate several defense mechanisms at the physiological, cellular, and molecular levels, which include a change in plant height and leaf size, upregulation of antioxidant defense enzymes, and increase in the levels of defense-related genes and proteins ( Nagamalla et al., 2021 ; Qamer et al., 2021 ).…”
Section: Proteomics and Stress Adaptation In Cottonmentioning
confidence: 99%
“…In other cases, plants subjected to repeated drought–rewatering cycles may recover and outperform plants without drought stress. For example, the aboveground and belowground biomass of Phalaris ( Phalaris aquatica ) were comparable to the well-watered controls after recovery from repeated drought treatment [ 20 ]. In another study, greater or similar tiller numbers and biomass were observed from perennial grass ( Leymus chinensis ) subjected to repeated moderate drought and severe drought intensities compared to the well-watered control treatment [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The tiller growth of perennial ryegrass is sensitive to drought stress [ 29 , 30 ]. However, there were several studies that mentioned that tiller development could recover or increase in grasses under a repeated drought–rewatering treatment [ 20 , 21 , 31 , 32 ]. A perennial ryegrass accession from Norway had 50% more shoot dry matter than the next best-performing accession after six drought cycles [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Climate conditions on mountains reflect variations in temperature and precipitation at relatively small spatial scales, providing a useful location for assessing environmental responses of leaf functional traits (Bai et al, 2022; Chieppa et al, 2022; Hikosaka et al, 2021). Indeed, temperature and precipitation control the plant leaf economics spectrum by affecting plant nutrient demand for various functions, soil nutrient supply (e.g., weathering, leaching, and organic matter accumulation), and nutrient reabsorption during leaf senescence (Chávez‐Vergara et al, 2015; Estiarte & Penuelas, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, Ge et al (2016) found that, compared with deciduous plants, evergreen plants have an advantage in nutrient‐poor soil due to their high nutrient recovery of senescent leaves. While changes in temperature and precipitation caused by different elevational gradients would inevitably lead to great variation in soil nutrient status (Chieppa et al, 2022; Hikosaka et al, 2021), it is still not clear whether the economic spectrum traits with changes in soil properties are coupled with this close relationship along elevational gradients. Additionally, mineral elements serve as key substrates for certain leaf functions (e.g., magnesium [Mg] is a key substrate for chlorophyll), which also considerably contributes to the leaf economics spectrum (Both et al, 2019; Verbruggen & Hermans, 2013).…”
Section: Introductionmentioning
confidence: 99%